Customized 2D Structures for High Throughput Electromigration Measurements. Issue 12 (18th June 2019) - Ravandi, Saeedeh; Zenger, Tobias; Eibelhuber, Martin; Hassel, Achim Walter; Mardare, Andrei Ionut
Abstract : Customized 2D wires are designed for high throughput electromigration testing on model Al and Cu thin films. Two direct writing approaches for defining the 2D wires are compared with photolithography. Electromigration effects on Al and Cu thin films are studied on 2D wires obtained applying both methods. A self‐developed four‐point probe is used to apply current through the test wires while measuring the potential drop along the wires. Photolithography is selected as the main method to outline the wires in order to have reproducible results in a high throughput manner. The errors of electromigration assessment are empirically evaluated by analyzing the data scattering for a large number of measured 2D wires. Inductively coupled plasma optical emission spectrometry (ICP‐OES) is performed on the photoresist removal solution before and after the lift‐off process. No traces of metallic elements are detected in both cases confirming the proposed mechanism. Abstract : Two dimensional wires are designed for statistical electromigration testing (Al and Cu) using three different approaches. A self‐developed 4‐point measuring head is used for the current‐voltage measurements. All three patterning approaches led to electromigration failure at high current densities between 0.4–0.8 MA cm −2 through a non‐linear behavior. The data scattering is evaluated for a large number of 2D wires.